2018
DOI: 10.15171/jcvtr.2018.25
|View full text |Cite
|
Sign up to set email alerts
|

Association of modified Nordic diet with cardiovascular risk factors among type 2 diabetes patients: a cross-sectional study

Abstract: Introduction: Cardiovascular disease (CVD) is one of the most important causes of mortality. Healthy diets can decrease CVDs and other chronic diseases especially in patients with type 2 diabetes. In this study, we investigate association between adherence to the modified Nordic diet and cardiovascular risk factors among patients with type 2 diabetes. Methods: This cross-sectional study was conducted among 339 type 2 diabetic patients. Anthropometric indices, blood pressure, and biochemical tests were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 26 publications
2
34
0
8
Order By: Relevance
“…Several dietary patterns assessed by the scoring system revealed a significant association with CVD risk factors. Adherence to the Nordic diet was associated with a reduction of LDL levels, blood pressure and the prevalence of obesity among 339 Iranian diabetic patients . Moreover, a study showed that the highest adherence to dietary quality indices such as the Mediterranean diet adherence score and the Prime diet quality score was associated with an improvement of lipid profiles and anthropometric measures among subjects who were overweight, obese and had metabolic syndrome .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several dietary patterns assessed by the scoring system revealed a significant association with CVD risk factors. Adherence to the Nordic diet was associated with a reduction of LDL levels, blood pressure and the prevalence of obesity among 339 Iranian diabetic patients . Moreover, a study showed that the highest adherence to dietary quality indices such as the Mediterranean diet adherence score and the Prime diet quality score was associated with an improvement of lipid profiles and anthropometric measures among subjects who were overweight, obese and had metabolic syndrome .…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to the Nordic diet was associated with a reduction of LDL levels, blood pressure and the prevalence of obesity among 339 Iranian diabetic patients. 37 Moreover, a study showed that the highest adherence to dietary quality indices such as the Mediterranean diet adherence score and the Prime diet quality score was associated with an improvement of lipid profiles and anthropometric measures among subjects who were overweight, obese and had metabolic syndrome. 38 Another study showed that a lower dietary quality, as assessed by adherence to the DASH (Dietary Approaches to Stop Hypertension), HDI (Healthy Diet Indicator) and the Mediterranean Diet Score, was associated with the developing prevalence of hypertension in Japanese male workers.…”
Section: Discussionmentioning
confidence: 99%
“…The NFI, less commonly used, is based on frequently consumed foods in the Nordic countries (the Scandinavian region), such as whole grains, fruits, low-fat dairy products, fatty fish such as salmon, and cabbage and root vegetables, with a focus on the intake of organic foods and healthy fat ( 100 ). The number of components included in the score range between 6 and 9 ( 48 , 71 ). The Nordic scoring system is relative and is based on distribution of intake above and below median consumption, with equal weights assigned to each category, and without applying a cutoff value for maximum intake.…”
Section: Country-specific Dietary Patterns and Associations With Cvdmentioning
confidence: 99%
“…Some studies have shown a signi cant decrease of hs-CRP [33,58], even after adjusting for weight loss [33]. In Fritzen et al research hs-CRP level decreased signi cantly after 26 weeks of Nordic diet intervention just in women group (39). It is noteworthy that our results cannot conclude to anti-in ammatory aspects of Nordic diet, since other in ammatory markers were not included in our study and there are not enough investigations about this issue yet.…”
Section: Discussionmentioning
confidence: 63%
“…In a cross-sectional study by Daneshzad et al ndings indicated a decrease in waist circumference in the highest adherence of modi ed Nordic diet compared to lowest level, but it was insigni cant. They also detected that the odds of higher BMI was signi cantly lower in the highest tertile of adherence in comparison to the lowest one [39]. The concomitant reduction in weight, BMI and waist circumference in Darwiche et al study indicate that anthropometric improvement can be induced by Nordic diet [36].…”
Section: Discussionmentioning
confidence: 90%